Methylated septin 9 gene for noninvasive diagnosis and therapy monitoring of breast cancer - Chen, Shen; Zhou, Changxin; Liu, Wei; Sun, Shanping; Zhang, Anqi; Tang, Wenqiang; Zhang, Shan; Zhang, Yang; Fu, Bo (Translational Cancer Research, 2018)
Background: Blood-based biomarkers specific for breast cancer is urgently demanded to facilitate the screening and reduce breast cancer-related deaths. This study evaluated the potential of methylated septin 9 gene (mSEPT9) as a biomarker for breast cancer. Methods: A total of 86 breast biopsy samples were collected from 59 patients with breast cancer and from 27 patients with benign breast tumor. Two hundred and seven plasma samples were collected from 80 patients with breast cancer, 27 patients with benign breast tumor patients, and 100 healthy volunteers. mSEPT9 was detected using the Epi proColon 2.0 CE test. Additionally, 40 tissue cases of the tumor samples were analysed by real time PCR for SEPT9_v2 mRNA expression and by immunohistochemical staining for SEPT9 protein expression. Serum CEA, CK19 and CA15-3 concentrations were analyzed using an Electrochemiluminescence Immunoassay Kit. Results: The sensitivity of plasma mSEPT9 for detecting breast cancer was 26.3% with a specificity of 97.6%. The plasma mSEPT9-positive rate was higher in patients with later stage lymph node metastasis (P=0.018), intravascular tumor thrombus (P=0.035), ki67-positive (P=0.033) and p53-positive (P=0.044). Despite its limitation in sensitivity, conversion of plasma mSEPT9 to negative status in mSEPT9-positive breast cancer patients following cancer treatment was correlated with favorable responses, while persistent positivity was associated with poor responses. mSEPT9 performed comparably with CK19 (P>0.05) and better than CEA (P=0.002) and CA15-3 (P